Dampak Media Sosial terhadap Kejujuran Remaja pada Orang Tua di Desa Stabat Lama Barat - Delima Novasaria; Lahmuddin Lahmuddin (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
This study uses a qualitative method with a descriptive approach to examine the impact of social media on the honesty of teenagers toward their parents in Stabat Lama Barat Village. The aim of this research is to describe the extent to which the use of social media influences teenagers’ honest behavior in communication and interaction with their parents. In an increasingly advanced digital era, social media is not only a source of entertainment but also has a significant influence on character development and moral values, including honesty. The results show that some teenagers tend to hide their social media activities from their parents, either due to privacy concerns, fear of being scolded, or the desire to create a certain image online. This behavior leads to reduced openness and honesty in their daily lives. However, there are also teenagers who are able to use social media wisely while upholding honesty within the family. Factors such as moral education at home, parenting styles, and social environment play an important role in shaping honest attitudes among teenagers despite the rapid growth of digitalization.